Analisis Faktor Risiko Kejadian Stunting Pada Balita Di Kelurahan Mangasa Kota Makassar - Nurul Ulfah Mutthalib; Ernasari (MEDIA ILMU KESEHATAN, 2025)
Background: The incidence of stunting in the world reaches 22%, more than half is from Asia. The Indonesian Ministry of Health, 2023 reported that the prevalence of stunting in 2022 was 21.6%. SSGI 2022 noted that South Sulawesi was the 10th highest of stunting in Indonesia (27.2%). Mangasa Health Center is the highest contributor stunting (202) in 2024.Objective: To analyze the risk factors of stunting in Mangasa Village, Tamalate Sub-district, Makassar City.Methods: It is the observational research with case control design. The population was 960 people, a sample of 24 stunting toddlers and 24 non-stunting toddlers using purposive sampling technique and instruments using questionnaires.Results: The results showed that the variables of feeding practices (OR: 0.217 CI (LL: 0.022, UL: 2.108)), psychosocial stimuli (OR: 0.455 CI LL: 0.075, UL: 2.756), Environmental Sanitation (OR: 0.716 CI LL: 0.716), UL: 2.229) and Occupant hygiene behavior (OR: 0.429 CI LL: 0.302, UL: 0.608) are not risk factors for stunting in Mangasa Makassar but as protective factors which can prevent stunting.Conclusion: All variables are not risk factors but protective factors. Promotive, preventive and advocacy efforts to be further enhanced in the Mangasa Village area of Makassar City.